Metode Forward Chaining Untuk Penentuan Kelayakan Bisnis Usaha Mikro - Kurniadi, Dedy; Prahasto, Toni; Widiyanto, Ibnu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2016)
In this present study has done business feasibility of the micro industrial sector based on the importance of Business Feasibility Study (BFS) on business organization that requires an assessment of the business feasibility process as a benchmark for investors or business owners and also to minimize the business risks that may occur at a later date to be addressed appropriately. This study aims to create a Business Feasibility Information System (BFIS) using a forward chaining. Forward chaining method has a high success rate when applied in various fields. Forward chaining developed for excellent performance in solving various problems. The process of doing a forward chaining requires input variables. The input process covers legal aspects human resources and management environmental aspects marketing aspects aspects of production and financial aspects. Six variables are processed in the database that was later acquired data using inference machine to form a pattern of reasoning that is assembled using forward chaining algorithm. Further reasoning patterns are registered into a database rule to get the address data. Results from this study is a Decision Support System (DSS), which can give a decision on the feasibility assessment and business micro-enterprises in the industrial sector. This device can be developed to help entrepreneurs and investors in the micro industrial sector to assess their business activities